Celebrating the success of UMP's leading researchers in the seventh Cendekia Bitara Award - Noor Syahidah, Sabran; Ernie Nurazlin, Lizam (Penerbit UMP, 2015)
Universiti Malaysia Pahang (UMP)'s Seventh Cendekia Bitara Award which took place at Hyatt Hotel in Kuantan on April 27, 2015 showcased the accomplishments of its academic staff.